LAND USE CHANGE, WATERSHED DEGRADATION, AND THE ROLE OF NATURE-BASED SOLUTIONS IN FLOOD RISK REDUCTION IN THE CIMANDIRI WATERSHED, WEST JAVA, INDONESIA - Sandy Lesmana; Atie Trijuniati; I Nyoman Teguh Prasidha (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2026)
Flood occurrence in tropical watershed systems is increasingly linked to structural landscape transformation and declining ecological regulation capacity. In the Cimandiri Watershed of West Java, rapid land conversion over the past three decades has altered hydrological processes and intensified downstream vulnerability. This research investigates long-term land use transitions (1990–2024), evaluates watershed degradation using weighted biophysical indicators, and identifies strategic zones for ecosystem-based flood mitigation. Spatial analysis integrating land use, slope gradient, and critical land status reveals that 42.44% of the watershed area is categorized as moderately to highly degraded. Built-up land expanded almost fourfold during the study period, while forest cover declined substantially, indicating a shift from infiltration-dominated to runoff-dominated hydrological behavior. Areas with elevated degradation levels spatially correspond to zones of recurrent flood exposure in downstream and coastal sectors. The study proposes targeted implementation of Nature-Based Solutions (NbS), including upstream reforestation, riparian buffer restoration, and downstream retention enhancement, as a complementary strategy to conventional infrastructure. The findings emphasize that flood risk in Cimandiri is a systemic watershed issue shaped by cumulative upstream–downstream interactions rather than isolated local factors